2015
DOI: 10.4137/cmo.s29462
|View full text |Cite
|
Sign up to set email alerts
|

Galectin-3 as a Potential Target to Prevent Cancer Metastasis

Abstract: Interactions between two cells or between cell and extracellular matrix mediated by protein–carbohydrate interactions play pivotal roles in modulating various biological processes such as growth regulation, immune function, cancer metastasis, and apoptosis. Galectin-3, a member of the β-galactoside-binding lectin family, is involved in fibrosis as well as cancer progression and metastasis, but the detailed mechanisms of its functions remain elusive. This review discusses its structure, carbohydrate-binding pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
106
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 98 publications
(107 citation statements)
references
References 138 publications
(220 reference statements)
1
106
0
Order By: Relevance
“…The presence of gal-3 expression is also a proved phenomenon for thyroid carcinomas, as we report in this present study as well, and it has been found that the malignant transformation of thyroid cancer is clearly associated with increased gal-3 expression [De Matos et al, 2012]. The promoter region of the gal-3 gene has several regulatory elements such as GC box, CRE motif, AP-1 region, and NF-kB [Ahmed et al, 2011]. Thus, the active role of gal-3 that plays in many cancer-related cellular processes has gained attention to which mechanisms regulates its expression associated with the transcriptional level.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…The presence of gal-3 expression is also a proved phenomenon for thyroid carcinomas, as we report in this present study as well, and it has been found that the malignant transformation of thyroid cancer is clearly associated with increased gal-3 expression [De Matos et al, 2012]. The promoter region of the gal-3 gene has several regulatory elements such as GC box, CRE motif, AP-1 region, and NF-kB [Ahmed et al, 2011]. Thus, the active role of gal-3 that plays in many cancer-related cellular processes has gained attention to which mechanisms regulates its expression associated with the transcriptional level.…”
Section: Discussionsupporting
confidence: 83%
“…Most of the studies have been pointed out that the gal-3 molecule contributes to those common phenotypic characteristics of malignancy [Ahmed et al, 2011]. Most of the studies have been pointed out that the gal-3 molecule contributes to those common phenotypic characteristics of malignancy [Ahmed et al, 2011].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the nucleus, STAT3 binds to target genes and induces the transcription of several genes associated with cell proliferation and anti-apoptosis [48, 49]. We have been working on the gene regulation and functional characterization of galectin-3 over the years [16, 31, 46, 5456]. Several studies suggest that galectin-3 is involved in tumor cell adhesion, proliferation, angiogenesis, cancer progression and metastasis [13, 1620].…”
Section: Discussionmentioning
confidence: 99%
“…So far, actual pathophysiological mechanisms of delirium remain unclear, but a growing body of evidence indicates inflammation might play an important role (Cerejeira, Firmino, VazSerra, & Mukaetova-Ladinska, 2010;Cerejeira, Nogueira, Luís, VazSerra, & Mukaetova-Ladinska, 2012;Dillon et al, 2017). Galectin-3, a member of the β-galactoside-binding galectin family, is uniquely chimeric (Ahmed & AlSadek, 2015;de Oliveira et al, 2015). Originally, galectin is found to be involved in multiple aspects, including cell adhesion, proliferation, clearance, apoptosis, cell activation, cell migration, and phagocytosis (Li, Li, & Gao, 2014;Peacock & DiSomma, 2014).…”
Section: Introductionmentioning
confidence: 99%